Gus Yahya and the NU’s New Path: Note on the 34th Congress - Zezen Zaenal Mutaqin (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2022)
The 34th Nahdlatul Ulama (NU) Congress in Lampung was organized in an unusual situation. It was the first kind of NU congress organized in the era of a global pandemic. The date of congress itself was a subject of controversy and debated by competing candidates due to the lockdown, a standard measure taken by the government to control the spread of the Covid-19 virus. There was even an idea to postpone the congress altogether and asked K.H. Said Aqil Siradj, the incumbent leader, to stay indefinitely until the situation is back to normal. However, after a tussle and negotiation, finally, all factions agreed that the congress would be organized at the initial date planned by the Central Board of NU (Pengurus Besar Nahdlatul Ulama, PBNU), which was at the end of December (22-23 December 2021). At that time, the case of Covid-19 was relatively low, and the gap was perfect for a congress.